Investment relationship corporate social responsibility and profitability of insurance enterprises - Hai, Tran Van; Quang, Nguyen Van; Cu, Hoang Manh; Anh, Tran Thi Lan (Asian Journal of Economic Modelling, 2025)
The objective of this study is to clarify the impact of social responsibility on the profitability of insurance companies operating in Vietnam. As a service business, the vessel absorbs risk for the economy. The database was collected online by the authors. The survey period was from May 2024 to November 2024. Secondary data were collected from 2013 to 2023. The research results were based on 712 responses from insurance company employees, insurance consumers, and domestic insurance experts. Using quantitative research methods, PLS-SEM linear structural modeling was performed using SPSS and AMOS 20 software. The results indicate that CSR is positively correlated with the profitability of insurance businesses, primarily through the responsibility of insurance companies to consumers. Recommended solutions include: 1) Commitment to the quality of CSR reporting; 2) Protecting consumer rights through model transaction contracts; 3) Implementing a code of business ethics; 4) Addressing issues in the insurance compensation settlement process. The study supplements basic theories for insurance businesses and recommends that they actively invest in CSR programs to enhance profitability.